The orality in the Civil Justice: A real engagement promoted by the civil judges - Bustamante Zegarra, Ramiro Antonio (2020)
The Peruvian republican legal stile has influenced the Spanish and French legal tradition. It was characterized by the formal and textual Justice. Rather, the new legal style is changing the old paradigm and it proposes oral litigation. Now this influences the framework of the Civil Justice. This recent change means adopting the principles of immediacy and the central role of the judge to guide the process. Consequently, this new perspective requires the reorganization of the judicial office and new standards in the Legal Process. The behavior of public officials and lawyers is changing. Some benefits come with this new legal model, for example, it serves to end a judicial dispute in a short time. The orality in a Civil Justice is a new experience: the initiative has been carried out by civil judges, they have not waited for the executive or legislative branch to modify the Civil Procedure Law of 1993. This initiative benefits the civil judicial system.